Variables that influence the application of precision agriculture in Colombia: review of studies - Pérez-Ortega, Diego Javier; Bolaños-Alomia, Fabio Andrés; da Silva, Alexandre Marco [UNESP] (Corporacion Colombiana de Investigacion Agropecuaria (Corpoica), 2022)
This article sought to identify the main variables that influence the adoption of precision agriculture (AP) technologies described in the literature. In this sense, a systematic bibliographic review was carried out in three databases (Scopus, Web of Science and Scielo), combining the terms Precision Agriculture, Application or Adoption, Technologies and crops. The search yielded more than 60 documents that were submitted to filters for pre-established exclusions. As a result of these filters, 11 articles were selected for analysis, which allowed the identification of AP technology application analysis contexts in Colombia. The results show that ease of use and perceived utility are the main aspects of the use of PA technologies. On the other hand, the variables related to the characteristics of the producer and the property are the main determinants of adoption linked to the ex post context.
Variables que influyen en la aplicación de la agricultura de precisión en Colombia: revisión de estudios
Keywords: databases; precision agriculture; sustainable production; technology adoption; variables of influence